Glutamate synthesis in Streptomyces coelicolor. - Fisher, S H (1989)
Both glutamate synthase (GOGAT) and glutamate dehydrogenase (GDH) are involved in glutamate synthesis in Streptomyces coelicolor. The highest levels of GDH were seen in extracts of cells grown with high levels of ammonium as the nitrogen source. GOGAT activity was reduced two- to threefold in extracts of cells grown with good sources of glutamate. S. coelicolor mutants deficient in GOGAT (Glt-) required glutamate for growth with L-alanine, asparagine, arginine, or histidine as the nitrogen source but grew like wild-type cells when ammonium, glutamine, or aspartate was the nitrogen source. The glt mutations were tightly linked to hisA1. Mutants deficient in both GOGAT and GDH (Gdh-) required glutamate for growth in all media. The gdh-5 mutation was mapped to the left region of the S. coelicolor chromosomal map, between proA1 and uraA1.